DESIRE, IDENTITY, AND THE SUPEREGO: A FREUDIAN ANALYSIS OF MIGUEL’S PSYCHOLOGICAL JOURNEY IN PIXAR’S COCO (2017) - Fisya Ananta Sheila Ningrum (CV Grasta Glory, 2025)
This analysis focuses on Miguel, the protagonist of the film Coco (2017), and his development throughout the narrative. Utilizing Sigmund Freud's framework of the psyche—which includes the id (instincts), ego (self-control), and superego (ethical constraints) this research elucidates Miguel’s internal struggles. Initially, Miguel’s family prohibits music due to a distressing history. This familial decree, primarily upheld by his grandmother, symbolizes the superego. Conversely, Miguel possesses an intense passion for music, representing his id, or intrinsic yearning. As he ventures out to pursue his aspirations, he begins to clarify his values and priorities. In the Land of the Dead, Miguel discovers how to reconcile his passion for music with his affection for his family, illustrating the emergence of the ego guiding his choices. Through significant symbols like the guitar and family photograph, the film depicts Miguel mending familial scars and uncovering his authentic identity. This research demonstrates that Coco transcends mere musical themes; it is an impactful narrative about kinship, personal identity, and the pursuit of one’s desires. The findings indicate that Miguel’s internal journey reflects Freud’s structural theory of personality, illustrating how animated films can portray complex psychological development. This contributes to a deeper understanding of identity formation in family-centered narratives within popular media.